Dampak Pembelajaran Daring terhadap Motivasi Belajar Mahasiswa Teknologi Pendidikan Angkatan 2023 - Abril Munadhil Alkhoir; Ilham Nawawi; Mohammad Meidy Abrar Nurjasir; Zaid Faturrahman Syafari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Technological developments bring about change. One of the changes occurring in the education sector is online learning. Online learning allows learning activities between teachers and students to take place without meeting face to face in class and can take place at any time as long as there are devices such as smartphones, laptops and computers that are connected to the internet. Implementing online learning will certainly have a different influence from direct classroom learning. Therefore, this research was conducted with the aim of exploring the impact of online learning on the learning motivation of educational technology students class of 2023. This research was conducted using quantitative methods, by distributing questionnaires to educational technology students class of 2023, then the data was processed using Microsoft Excel. The aim of this research is to determine the impact of online learning on learning motivation. In this research, it was found that the number of learning motivations in online use was decreasing and the understanding of learning material was low when implementing online learning. Online learning has a big influence on the learning motivation of educational technology students class of 2023.